2014
DOI: 10.4028/www.scientific.net/amm.592-594.874
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Hardwickia Binata Fiber with Epoxy

Abstract: For hundreds of year’s composite materials have been playing very crucial role in the field of materials. The applications of composites expanded widely to the aircraft, automotive, sporting goods, and biomedical industries. Today natural fibers like ramie, jowar, sisal, flax, hemp, jute, bamboo, banana, etc. are widely used than the synthetic fibers like glass, carbon, ceramic fibers, etc., because these natural fibres offer several advantages over synthetic fibres. In this project a new natural fiber is intr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…The ventilation system in rotor provides better temperature dissipation [13,14]. The ventilated rotor reduces the temperature, stress and deformation [15].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The ventilation system in rotor provides better temperature dissipation [13,14]. The ventilated rotor reduces the temperature, stress and deformation [15].…”
Section: Literature Reviewmentioning
confidence: 99%
“…21,3234 In addition, recent research has shown that surface treatment is an effective technique for changing the microstructure at the fiber–matrix interface in both laminate and fiber-reinforced composites, and can improve their final performance. 35…”
Section: Introductionmentioning
confidence: 99%